2020
DOI: 10.1038/s41598-020-77450-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma hinders erythropoiesis and causes anaemia owing to high levels of CCL3 in the bone marrow microenvironment

Abstract: Anaemia is the most common complication of myeloma and is associated with worse clinical outcomes. Although marrow replacement with myeloma cells is widely considered a mechanistic rationale for anaemia, the exact process has not been fully understood. Our large cohort of 1363 myeloma patients had more than 50% of patients with moderate or severe anaemia at the time of diagnosis. Anaemia positively correlated with myeloma cell infiltration in the bone marrow (BM) and worse patient outcomes. The quantity and er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…Thus, the potential of erythroid differentiation of HSCs is commonly suppressed, especially in the bone marrow. EPC precursors, MEPs, are the most suppressed progenitor cells in the bone marrow of mice with hematological malignancies [ 57 , 58 , 136 , 140 , 152 , 153 , 154 ]. In plasma cell myeloma, malignant cell infiltration correlates negatively with hemoglobin concentration, but not with leukocytes or platelet counts, which suggests the selective impairment of erythropoiesis by malignant cells [ 155 ].…”
Section: Cancer-induced Dysregulation Of Erythropoiesismentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the potential of erythroid differentiation of HSCs is commonly suppressed, especially in the bone marrow. EPC precursors, MEPs, are the most suppressed progenitor cells in the bone marrow of mice with hematological malignancies [ 57 , 58 , 136 , 140 , 152 , 153 , 154 ]. In plasma cell myeloma, malignant cell infiltration correlates negatively with hemoglobin concentration, but not with leukocytes or platelet counts, which suggests the selective impairment of erythropoiesis by malignant cells [ 155 ].…”
Section: Cancer-induced Dysregulation Of Erythropoiesismentioning
confidence: 99%
“…TGF-β induces the maturation arrest of early-stage EPCs by noncanonical activation of p38, which in turn triggers GATA1 degradation [ 57 , 58 , 140 ]. Moreover, TGF-β activates SMAD2 and SMAD3 via the type III TGF-β receptor, which is transiently upregulated in early-stage EPCs [ 178 ].…”
Section: Cancer-induced Dysregulation Of Erythropoiesismentioning
confidence: 99%
See 2 more Smart Citations
“…ROS also may decrease CD3ζ in T-cells 29 We further demonstrated that EPCs expand in anemic patients and suppress T-cells. Anemia correlates with worse outcomes in many diseases, including pneumonia 30 or cancer 31 . Moreover, preoperative anemia is associated with an increased risk of infection and mortality in patients undergoing surgery 32, .…”
Section: Discussionmentioning
confidence: 99%